Improving the corrosion resistance of micro-arc oxidation coated Mg–Zn–Ca alloy. Issue 14 (26th February 2020) - Chen, Yang; Dou, Jinhe; Pang, Zengfen; Yu, Huijun; Chen, Chuanzhong; Feng, Jinkui
Abstract : Large amount of micro-pores formed in MAO coatings were interconnected and sealed. Abstract : Four additives (Na2 WO4, nano-hydroxyapatite, K2 TiF6 and NaF) were added into the Na5 P3 O10 + NaOH + C3 H8 O3 base electrolyte according to the orthogonal design of four factors three levels (L9 (3 4 )). Nine different micro-arc oxidation (MAO) coatings were fabricated on Mg–2Zn–0.5Ca alloys through orthogonal experiments. The effects of four additives on the microstructure, mechanical properties, corrosion resistance and biocompatibility of MAO coatings were investigated through X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS), electrochemical corrosion test and in vitro degradation test. The addition of nano-hydroxyapatite and K2 TiF6 showed self-sealing effects and contributed to the corrosion resistance of the samples significantly. The addition of 0.5 g L −1 Na2 WO4 markedly elevated the bonding strength of the coatings with the substrate. The optimal combination of factors and levels considering both mechanical properties and corrosion resistance was: 0.5 g L −1 Na2 WO4, 0 g L −1 NaF, 5 g L −1 n-HAp, 5 g L −1 K2 TiF6 . The growth mechanism of MAO coatings combining with the visual phenomenon was discussed as well.